Media usage among the coastal communities in Malaysia - Chew, Chun Meng; Omar, Siti Zobidah; Kamaruddin, Nurani; Bolong, Jusang; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril (Canadian Center of Science and Education, 2014)
The main objective of this paper was to identify the preferred media tool and its usage among coastal communities in Malaysia. Data were collected using a questionnaire completed by a total of 210 people from the selected coastal communities. The findings indicated that people living and working in the Malaysian coastal communities, rely more on mobile phones and television to access relevant information. The results also suggest the need for improving the living standard of the rural communities living in the coastal areas of Malaysia. The use of advanced media tools could enhance living conditions and economy standards; as well as to address the communication needs in the coastal communities in Malaysia.